A comparison study of local lattice distortion in Ni80Pd20 binary alloy and FeCoNiCrPd high-entropy alloy. (November 2018) - Tong, Y.; Zhao, S.; Jin, K.; Bei, H.; Ko, J.Y.P.; Zhang, Y.; Zhang, F.X.
Abstract: The effect of alloying Pd on the local lattice distortion (LLD) in the Ni and FeCoNiCr host matrixes is quantified by integrating local structure characterization and theoretical calculations. The local structure measurements reveal that the mean LLD in the FeCoNiCrPd high-entropy alloy (HEA) is twice as high as the Ni80 Pd20 binary alloy though the FeCoNiCr base alloy has a negligible mean LLD. Density functional theory calculations unveil that the unexpected high mean LLD in FeCoNiCrPd is related to the high fluctuation of LLD in the FeCoNiCr matrix. These observations suggest a synergetic effect of chemical complexity on HEAs' mean LLD. Graphical abstract: Unlabelled Image